2019
DOI: 10.9775/kvfd.2019.22856
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Sıcaklıklarda Depolanan Tavuk Yumurtalarının Kalite Parametrelerinin Değerlendirilmesi

Abstract: This study was carried out to evaluate the effect of temperature and time on the internal and external quality of chicken eggs stored at room and fridge temperature for 28 days. A total of 176 eggs of Lohmann Brown (LSL) laying hens were used for the study. The eggs from the same batch were stored at fridge (5°C) and room temperature (25°C), internal and external quality parameters and microbiological analyzes of eggs were evaluated on days 0, 1, 8, 18, 21 and 28. No coliform bacteria, E. coli and Salmonella s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Škrbić et al [43] reported that refrigerated temperatures lower the rate of increase in albumen pH compared to ambient temperature. However, Altunatmaz et al [35] found no significant effect of temperature on albumen pH after 28 d of storage. The increased pH at room temperature could be due to the increased escape of gases from eggs.…”
Section: Albumen Phmentioning
confidence: 96%
See 3 more Smart Citations
“…Škrbić et al [43] reported that refrigerated temperatures lower the rate of increase in albumen pH compared to ambient temperature. However, Altunatmaz et al [35] found no significant effect of temperature on albumen pH after 28 d of storage. The increased pH at room temperature could be due to the increased escape of gases from eggs.…”
Section: Albumen Phmentioning
confidence: 96%
“…This decrease in albumen weight was due to a decrease in the thick albumen weight and an increase in yolk weight, suggesting that water diffused from the albumen through the vitelline membrane into the yolk during storage. Albumen weight loss is higher at room temperature than under low temperatures [35] because of higher water loss from the albumen to the yolk. A drastic reduction in AH over storage time indicates poor albumen quality and adversely influences HU values.…”
Section: Albumen Heightmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, some studies have demonstrated that pathogens not detected on the outer surface of the eggshell can be present in the eggshell pores and membranes (Chousalkar et al, 2010;Chousalkar and Roberts, 2012). Previous studies in Turkey have been mostly focused on microbiological assessment of retail eggs produced from conventional caged-layers (Erkan et al, 2008;Temelli et al, 2015;İncili et al, 2019;Sandikci et al, 2020). To the authors' knowledge, there are limited data available on comparative microbial analysis of the eggshell surface, eggshell (pores and membranes), and egg yolk of retail organic eggs, free-range eggs, barn eggs and conventional-cage eggs.…”
Section: Introductionmentioning
confidence: 99%